Colony stimulating factor-induced differentiation of murine M1 myeloid leukemia cells is permissive in early G1 phase. - Tsuda, H (1986)
Granulocyte-colony stimulating factor (G-CSF) induces differentiation of M1 murine myeloid leukemia cells into mature granulocytes/macrophages and also causes accumulation of the cells in the G1 phase of the cell cycle. We examined, therefore, whether synchronization of M1 cells in the G1 phase could affect G-CSF-induced differentiation as quantitated by expression of Fc fragment receptors (FcR) and lysozyme activity. Cells were arrested in early G1 by density inhibition in the absence of serum and in late G1 by addition of aphidicolin. Cells synchronized in early G1, when stimulated with G-CSF, showed enhanced expression of FcR and lysozyme activity. Eighty percent of the cells expressed FcR 18 hr after addition of G-CSF while, in exponentially growing cells, this percentage was reached 72 hr after addition of G-CSF. Cells synchronized in late G1 did not show enhanced expression of differentiation markers. These results imply that with respect to G-CSF-induced differentiation, the G1 phase can be separated into an early permissive and a later nonpermissive stage.